1990
DOI: 10.1111/j.1365-4362.1990.tb03837.x
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Effects of a Pulsed Electrostatic Field with Specific Reference to Hair Electrotrichogenesis

Abstract: This comparative, controlled study demonstrates the positive biologic effect on hair regrowth of a pulsed electrical field administered according to a regularized treatment schedule over 36 weeks. Mean hair count comparisons within the groups significantly favor the treatment group, which exhibited a 66.1% hair count increase over baseline. The control group increase over baseline was 25.6%. It is notable also that 29 of the 30 treatment subjects (96.7%) exhibited regrowth or no further hair loss. The process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Four trials for pulsed electrostatic field could be included into the evidence‐based evaluation of the guideline [98–101]. Though the trials showed modest increase in total, anagen or nonvellus hair counts, the use in clinical routine is doubtful due to unfavourable cost‐benefit ratio.…”
Section: Therapeutic Options and Therapy Assessmentmentioning
confidence: 99%
“…Four trials for pulsed electrostatic field could be included into the evidence‐based evaluation of the guideline [98–101]. Though the trials showed modest increase in total, anagen or nonvellus hair counts, the use in clinical routine is doubtful due to unfavourable cost‐benefit ratio.…”
Section: Therapeutic Options and Therapy Assessmentmentioning
confidence: 99%
“…Previous studies using high-voltage pulsed galvanic stimulation showed that the electrical stimulus induced cell migration and wound repair through increased protein and DNA synthesis [11]. Maddin et al demonstrated that a pulsed electrostatic field had positive biological effects on hair re-growth but the biophysical mechanism was not clear [12].…”
Section: Introductionmentioning
confidence: 99%
“…Good results were obtained: out of 13 study patients hair loss was noted in just one person and it was only partial. No adverse effects of ETG or negative sensations of patients undergoing treatment have been reported [28][29][30].…”
Section: Electrotrichogenesismentioning
confidence: 99%
“…Due to appropriate electric field distribution, the highest drop in voltage is at the scalp surface, with minimal exposure in deeper parts of the head. In physical terms the method seems perfectly safe: electric field intensity (4000 V/m) represents 2% of the level determined as safe in experiments conducted on animals exposed to an electric field for more than 10 months, and only 0.001% of the value recognized as dangerous [28].…”
Section: Electrotrichogenesismentioning
confidence: 99%
See 1 more Smart Citation